The emergence of professional learning networks in Spain. Issue 1 (21st January 2019) - Azorín, Cecilia
Abstract : Purpose: The purpose of this paper is to construct a policy map of professional learning networks (PLNs) in Spain. It includes initiatives prompted in Spanish schools in which social, political, cultural and educational elements are integrated. At the same time, it analyses which organization promotes each of the networks, the objectives pursued and the scope of the network in the territory in which it is created. Design/methodology/approach: The methodology followed is essentially descriptive and incorporates the first experiences with school networks which have been disseminated in the Spanish literature. It stimulates reflection on the role networks are expected to play in relation to local developments in this specific school system. Findings: The cases described (Castellon, Catalonia, Malaga and Seville) suggest a way forward for practitioners to advance toward an educational paradigm based on greater collaboration. This includes a partnership approach among professionals within and across classrooms, schools, communities, districts and education systems. In particular, the results place the focus of the network on the prevalence of the following school classification, included schools (community networks linking to the territory), extended schools (socio-educational networks), equity schools (equity fostering networks) and partnership schools (school-to-school support networks), whose objectives and scopes are reviewed. Research limitations/implications: With the Spanish context in mind, it is essential to recognize that more empirical evidence is still needed to make a significant contribution toward building knowledge in this research line. Indeed, sustainability seems to be an important point to consider in a short-term world where quick-fix solutions are required. However, PLNs need time to know how beneficial they really are, for example, in terms of student outcomes and school improvement. Practical implications: The argument developed assumes networks as a mirror wherein the present and future of education takes place. In this sense, the scientific and educational communities have both a challenge and an opportunity to rethink the potential of networking and collaboration in education. The article tries to be attractive to a specialized reader or one simply interested in the problem of networks in education and the reality of PLNs in Spain. Social implications: The network society demands a network school environment where communities are part of a local character strategy. Originality/value: This document offers an interesting view on networks that not only focus on education but on social and welfare issues and it aims to target education from a broader perspective; so resulting in opening schools to the community, which is not a widely covered topic in education research. In summary, the paper can be considered as a pioneer study in the Spanish context, which contains valuable information about PLNs, their origin and current status in this part of the world.